Clinical masks of marble disease - O. G. Radaikina; A. A. Usanova; I. Kh. Fazlova; N. N. Guranova; E. V. Radaikina (Современная ревматология)
Marble disease, or osteopetrosis (OPT), is rare in the practice of a rheumatologist, internist or pediatrician. This group of hereditary diseases is based on a defect in the formation, development and functioning of osteoclasts (OCL), which leads to disruption of the processes of resorption and remodeling of bone tissue. Disturbance of resorption leads to increased density and changes in the quality of the bones, as a result of which they become more fragile. As a rule, the disease manifests with pathological fractures. In recent decades, 70% of patients with OPT have been found to have mutations in at least 10 genes that lead to impaired functioning of the OCL. Depending on the variant of inheritance, autosomal dominant, autosomal recessive and intermediate types of OPT are distinguished. Autosomal dominant OPT has a benign course that can be asymptomatic or characterized by multiple bone fractures and other spinal anomalies. The disease usually manifests in adulthood or adolescence. Life expectancy in patients of this group does not differ from that in the general population. Malignant, or infantile, OPT is associated with an autosomal recessive inheritance pattern. Its clinical manifestations are observed from the moment of birth, without treatment, patients die within the first decade of life. In such patients, in addition to the skeletal pathology, there is involvement of the hematopoietic system, compression of the cranial nerves and their function disturbance.The article presents a clinical case of autosomal dominant OPT diagnosed in adulthood (at the age of 38), when the patient referred to the doctor for the first time. Differential diagnosis with ankylosing spondylitis and paraneoplastic spondyloarthritis was performed.